Os ritmos tradicionais nos tambores do tocantins: constituições identitárias e processos culturais - Araújo, Wendy Almeida de (2013)
The guiding theme of this research is the appropriation of traditional rhythms of Tocantins on a percussive music project called Tocantins Drums. The empirical corpus is a set of rhythms: sússia, catira, drum, roda and congo. The choise was motivated because they have cultural reference in the State. The goal was identify the Tocantins Drums group formation and appropriate. For this purpose was achieved, it was proposed specifically: understand the importance of the relationship between culture and communication and subaltern culture and mass culture; identify which group's proposal and how the rhythms are worked; understand how to constitute the identities of the group, to identify the elements and belonging of the project participants; verify that the more traditional groups are recognized in the representation of the Drums of Tocantins and realize what the differences between them.The assumptions were that participants in the group Drums of Tocantins developed from a traditional style, but incorporating elements of mass culture, its own forms and styles of cultural expression and acquired a positive stance in relation to the rhythms and music critics as massive , which could result in the construction of their identity.After the conclusion of the proposed research, it was found that not exacly those factors constitute the identity of the group, but a greater bond, the social inclusion.